Meaning Beyond Text: A Study on Symbolic Communication on Social Media - Saralde, Jessa Mae; Oñate, Rafael (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined symbolic communication on social media among Grade 11 Senior High School students of Polangui General Comprehensive High School during School Year 2025–2026. Anchored on Symbolic Interactionism Theory, Medium Theory, Social Semiotics Theory, and the researcher’s Dynamic Triadic Symbolic Communication Theory, the study explored how students construct and interpret meanings through digital symbols such as emojis, memes, GIFs, hashtags, and reaction icons. A descriptive–qualitative research design was employed using a survey questionnaire and narrative interviews. The respondents were 200 Grade 11 students selected through purposive sampling, while the data were analyzed using percentage, frequency count, rank order, weighted mean, and thematic analysis. The findings revealed that digital symbols carried varied meanings depending on personal experience, context, relationship, platform use, and cultural background. The heart emoji was mostly associated with appreciation or gratitude, the thumbs-up emoji with acknowledgment, the laughing emoji with humor, the crying emoji with sadness or emotional reaction, the folded-hands emoji with prayer or request, and the angry emoji with anger. Digital symbols were found to affect clarity, tone, and interpretation by serving as emotional cues, visual aids, and substitutes for nonverbal communication, although they may also lead to misinterpretation when users assign different meanings. The study concluded that symbolic communication reflects cultural and educational implications and supports the need to strengthen learners’ digital literacy and communication competence. Based on the findings, a proposed supplementary learning material on Effective Communication was developed. The study aligns with SDG 4, SDG 9, SDG 10, and SDG 16 by promoting quality education, digital readiness, inclusive communication, and responsible online interaction. Its sustainability impact lies in supporting educational, digital, cultural, institutional, and community sustainability through improved symbolic awareness and ethical digital communication.
Keywords: Communication Competence; Digital Literacy; Digital Symbols; Effective Communication; Emojis; Supplementary Learning Material; Symbolic Communication